Роздрібна торгівля в україні: стан, тенденції та інституційні заходи селективного регулювання - Нікішина, О. В.; Щербак, А. В. (Odesa National University of Technology, 2023)
The article contains the results of research on the problems of optimization of state regulation in the retail trade in Ukraine. The trends in the development of retail trade in our country, the most important problems existing in this sector have been determined. The causes and consequences of the existence of unfair trading practices in the relationship between domestic retail chains and their suppliers have been clarified. The changes in the regulatory system in the EU associated with the adoption of Directive 2011/7 of 16 February 2011 on combating late payment in commercial transactions and Directive 2019/633 of 17April 2019 on unfair trading practices in n business-to-business relationships in the agricultural and food supply chain have been researched. Based on the analysis of the EU experience and the situation in our country, the necessity has been substantiated and the ways of transition to selective regulation of retail trade in Ukraine have been determined. Selective regulation provides for the purposeful influence of the state on the points of growth or gaps in commodity-financial flows in systems of vertically adjacent commodity markets. It has been proposed to limit administrative interference in the work of retail outlets, as well as to gradually reduce the scope of price regulation. At the same time, it is expedient to introduce regulation in certain areas where it has not yet been carried out. In particular, it has been proposed to establish a deadline for settlements under commercial agreements and prohibit unfair trading practices by implementing the norms of EU Directives 2011/7 and 2019/633 into domestic legislation. The necessity has been substantiated and the ways of improving the system of control over the activities of markets have been proposed. Measures have been proposed to make the rates for market services transparent and to force market owners to use registrars of settlement transactions and pay taxes. In order to accelerate the development of retail trade, it has been proposed to actively use economic mechanisms: supporting clusters, stimulating the expansion of branded trade, as well as facilitating the creation of self-regulatory organizations of entrepreneurs in the sector.